Geology, geochemistry and geochronology of the Pium Diopside-Norite, Carajás Province - Santos, Roseli Dias dos; Galarza, Marco Antonio; Oliveira, Davis Carvalho de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2013)
The Pium Diopside-Norite occurs at south of Carajás Basin. It is constituted by norites (± gabbronorites), quartz gabbros with variation to enderbites, and locally, cumulatic rocks. Contemporary relations (magma mingling) involving norite varieties have been observed, since norites occur both as angular enclaves with rectilinear contacts into quartz gabbro rocks, evidencing high viscosity contrast, and as swarm of rounded enclaves (blebs/autoliths) into hornblende gabbros. The geochemical data show that the Pium Diopside-Norite has FeOt enrichment compared with MgO, indicating its tholeiitic subalkaline nature, and a source from partial melting of peridotitic mantle. Diagrams used to infer tectonic setting show that these rocks have geochemical affinities with within-plate basalts and indicate a magmatic evolution process from norites to enderbites. Pb-Pb ages of around 2745 Ma are considered as the crystallization ages for these rocks. Sm-Nd analysis yielded TDM ages from 3.14 to 3.06 Ga and εNd (T = 2.74 Ga) values between -2.78 and -1.58, indicating involvement of crustal sources in their genesis. The model ages confirm an important Mesoarchean period of crust formation at Carajás Province.
Keywords: Pb-Pb; Sm-Nd; Major and trace elements; Pium Norite; Amazonian Craton